Financial Literacy and Tax Antagonism Among Academic Staff of Private Universities in Nigeria - Madugba, Joseph Ugochukwu; Egbide, Ben-Caleb; Obadiaru, David Essosa (Prabandhan: Indian Journal of Management, 2025)
Purpose : Tax payment is a legal responsibility of every qualified citizen, though it is without a compensatory benefit. Hence, there is a need to explore all incentives that possibly reduce the taxable income and tax liability of potential taxpayers. This study inspected the financial literacy and tax antagonisms of the academic staff of private universities in Nigeria. Methodology : A descriptive research design was used, and the theory of well-being was explored. The study population was 12,086 staff, out of which a sample of 387 was selected. Four hundred five-point Likert scale questionnaires were distributed among respondents, and 215 were retrieved. Findings : A significant outcome indicated that only the national housing fund was noteworthy. The study found that financial literacy was not a determining factor of tax antagonism among academic staff in private universities in Nigeria and suggested that proprietors of private universities in Nigeria should encourage financial education among their academic staff. Practical Implications : It was endorsed that proprietors of private universities in Nigeria should enlighten their staff on tax incentives that can be explored to lessen the effect of high taxes on their staff. Originality : This study has contributed to the extant literature as it successfully explored legal means enshrined in Nigeria’s Finance Act 2021 for individual tax reduction. It required private university staff to explore tax reductions available to reduce their tax liabilities.